Hubungan Budaya Perusahaan dengan Kepuasan Kerja Karyawan pada PT. “X”, Yogyakarta - Murdiasih Murdiasih (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2003)
Study was carried out with the objective to find outthe relationship between corporate culture and working satisfaction of the employees. Hypothesis was postulated that there is a positive relationship between the corporate culture and working satisfaction of the employees. The study used methodology comprising of 120 persons were taken as samples from 512 people total employees of “X”, a tanning factory who hade been worked at least for 6 months, and minimum level of junior high school education. As tools for data collection were questionnaire for corporate culture measurement and modified Minnesota Satisfaction Questionnaire for working satisfaction determination. Regression analysis of the data was applied for testing the relationship. Result of regression analysis showed that very significantly positive relationship. (r= 0,863 ; p = 0,000) between corporate culture and working satisfaction was found. In conclussion there is a positive relationship between corporate culture and working satisfaction of the employees.Key Words : corporate culture, employees, working satisfaction